2017
DOI: 10.1063/1.4990774
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent clustering of initially well-mixed buoyant particles on a free-surface by Lagrangian coherent structures

Abstract: Particles that float on the surface of a 3D incompressible turbulent flow are exposed to non-divergencefree properties that result in clustering and unmixing, a reversal of how turbulence normally acts to mix and dilute scalars. Particle clustering is dominated by Lagrangian processes that depend on the time history of the flow; this suggests that Lagrangian coherent structures (LCS) might serve as templates for cluster formation. In this study, non-divergence-free clustering is examined both experimentally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In multiparticle systems, free surface turbulence has a determining effect on the particles floating on the surface. Pratt et al [ 18 ] showed that Lagrangian coherent structures generated by a turbulent flow near the gas–liquid free surface cause clustering of the initially well-mixed buoyant particles floating on it. The results of another study [ 19 ] suggested the same phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In multiparticle systems, free surface turbulence has a determining effect on the particles floating on the surface. Pratt et al [ 18 ] showed that Lagrangian coherent structures generated by a turbulent flow near the gas–liquid free surface cause clustering of the initially well-mixed buoyant particles floating on it. The results of another study [ 19 ] suggested the same phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The outlet jet velocity is another factor that can be modified to change the strength of the turbulence. Pratt et al. (2017) observed that increasing the input voltage of the pumps (which controls jet velocity and subsequently changes the jet outlet Reynolds number) increased and the dissipation rate while remained nearly constant.…”
Section: Actuator-based Turbulence-generation Mechanismsmentioning
confidence: 98%
“…2015; Pujara et al. 2018; Tinklenberg, Guala & Coletti 2023), the dissolution of large particles (Oehmke & Variano 2021), clustering of particles (Pratt, True & Crimaldi 2017; Petersen, Baker & Coletti 2019) and the melting of ice in turbulence (McCutchan 2020). Table 4 lists the known facilities that use RJAs for zero-mean-flow turbulence generation with their concomitant turbulence characteristics.…”
Section: Actuator-based Turbulence-generation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC is often identified by the accumulation of positively buoyant material into patches on the surface at the regions of downwelling between pairs of counter‐rotating vortices (Yang et al 2014; Chang et al 2019). Such turbulent clustering of buoyant particles on a free surface is formed during LC as the two‐dimensional (2D) surface flow becomes non‐divergence‐free (Pratt et al 2017). These windrows are streaks of variable length (2 m to 1 km) aligned with each Langmuir cell oriented in the direction of the wind.…”
Section: Figmentioning
confidence: 99%